The Effect of Adiponectin on the Regulation of Filaggrin Expression in Normal Human Epidermal Keratinocytes - Choi, Sun Young; Kim, Min Jeong; Ahn, Ga Ram; Park, Kui Young; Lee, Mi-Kyung; Seo, Seong Jun (Annals of dermatology, 2018)
Adiponectin, an adipokine secreted from adipocytes, affects energy metabolism and also shows anti-diabetic and anti-inflammatory properties. Recent studies have reported that adiponectin plays a role in regulating skin inflammation. This study aimed to investigate the effect of adiponectin on the expression of (FLG) in normal human epidermal keratinocytes (NHEKs). NHEKs were serum-starved for 6h before being treated with adiponectin. Afterward, cell viability was assessed by MTT assay. We also treated with calcium, interleukin (IL)-4, and IL-13 to provide positive and negative comparative controls, respectively. Gene mRNA expression was quantified using real time reverse transcription polymerase chain reaction, and protein expression was evaluated using Western blot. To evaluate the relationship among mitogen-activated protein kinases (MAPKs), activator protein 1 (AP-1), and FLG, we also treated cells with inhibitors for MAPKs JNK, p38, and ERK1/2. and mRNA expression in NHEKs significantly increased after treatment with 10 µg/ml adiponectin. Adiponectin also restored and mRNA expression that was otherwise inhibited by treatment with IL-4 and IL-13. Adiponectin induced expression via AP-1 and MAPK signaling. Adiponectin positively regulated the expression of and could be useful as a therapeutic agent to control diseases related to disrupted skin barrier function.